Methodological Proposal for the Television Analysis of Scientific Information: Case Study of the University of Zaragoza - Ibarra Arias, Rocio; Marta Lazo, Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This research proposes a new methodology to analyze the process of transferring scientific information from when findings are produced in institutes and research groups until it reaches society. This case study focuses on the analysis of scientific information emerging in the Aragon Community. As fieldwork, press releases from the Science Culture Unit of the University of Zaragoza were analyzed and contrasted with their coverage in audiovisual media. The results show a limited presence of scientific news in the main news programs, with more interest in public regional channels. In conclusion, it is found that the lack of audiovisual resources and limited space hinders dissemination on television, while visibility in regional media is influenced by the criteria of informational proximity and institutional announcements.